Coordination and Setting of Overcurrent Relays on The PLTMG BMPP Nusantara 1 Generator - Ronal Siregar; Marceau Haurissa; Marselin Jamlaay (Universitas Darul Ulum, 2026)
The electrical power system can distribute electrical energy optimally if power plants generate electrical energy with high reliability. However, disturbances in the electrical system can affect reliability. Therefore, safety equipment is necessary. In electrical power systems, protection devices are used to minimize disturbances, and protection relays must function properly. One of the protection devices used in generators is an overcurrent relay. To avoid relay failure, it is important to evaluate the overcurrent relay and test the reliability characteristics of the relay. Based on the overcurrent relay coordination test results, the calculation settings show that the relay is capable of handling maximum and minimum short-circuit currents, but with the existing settings, the relay does not function properly at minimum short-circuit currents. The maximum short-circuit current is 17.185A, and the minimum fault current is 13.828A. Comparing the calculation results with the existing settings, there are differences: for the inverse relay, the primary setting current is 494A and the secondary setting current is 0.988A, while for the definite time relay, the primary current is 3.666A and the secondary current is 7.3A with a relay operating time setting of 0.5 seconds. Meanwhile, the primary setting current value for the definite time relay is 526A and the secondary current is 1.05A, while the primary setting current for the definite time relay is 1.173A and the secondary current is 2.34A with an operating time of 0.6s. In the inverse relay, the calculated setting current value is lower than the existing setting. For the definite-time relay, the test results show a faster operating time and a higher setting current compared to the existing conditions, so the calculated results have the potential to improve the reliability of protection against overcurrent faults. By evaluating existing relay settings against calculated minimum and maximum short circuit currents, this study identifies critical gaps in generator protection. The data suggests that current settings lack the necessary sensitivity for low level fault detection. Consequently, we developed more responsive inverse and definite time relay configurations. This approach enhances the overall dependability of the protection scheme and serves as a vital technical guide for engineers tasked with optimizing overcurrent relay coordination in complex power grids.